К вопросу о времени появления византийской поливной посуды в Херсонесе - Седикова, Л.В. (Материалы по археологии, истории и этнографии Таврии, 1998)
In scientific literature there is an opinion that the period of appearing glazed pottery in Chersonesos is the mid-9th - the second half of the 9th century (A.Jakobson, D.Talis). As the result of recent excavations of water-reservoir a complex of finds of the first half of the 9th century was revealed; it contained some samples of early Byzantine crockery. These are dishes, plates and small pots having analogies to Constantinopol complexes of the 7th - the mid-9th centuries (R.Stevenson, J.Hayes). Hence, in the first half of the 9th century Chersonesos got some types of glazed crockery rare for Byzantium.